Comparison of Physical Assault and Other Mechanisms of Injury among Trauma Patients Attending the Emergency Department of a Tertiary Hospital in a Low-and Middle-Income Country (IAHS Medical Journal, 2022)
Background : Injury management and trauma registry are undeveloped in many Low- and Middle-Income Countries (LMICs). The objectives of the study were to assess the injury pattern and compare physical assault with other mechanisms of injury in this region.Materials and methods : A cross sectional study was conducted among trauma patients attending in the Emergency Department (ED) of the largest tertiary referral centre in the South-Eastern Bangladesh from 1-15 September, 2019. Patients’ demography, time of arrival in the ED, time of injury, occupation, residence, mechanism, type, mode and site of injury, and outcome were analysed and compared between physical assault and other mechanisms of injury.Results : Among a total of 839 patients, males were 2.42 times more than females. Age ranged from 3 months to 100 years, median 27 years. Majority (52.7%) of the patients belonged to ages between 20 and 40 years. The most common mechanisms of injury were physical assault (230, 27.4%), Road-Traffic Accident (RTA) (196, 23.4%) and falls (146, 17.4%). Physical assault was the commonest mechanism (39.2%) in female and among all age groups except in more than 70 years of old. More physical assaults occurred at night than other mechanism (p